Metonymic event-based time interval concepts in Mandarin Chinese—Evidence from time interval words - Zhong, Lingli; Liu, Zhengguang (Frontiers in Psychology, 2022)
Starting from the overwhelming view that time is metaphorically conceptualized in terms of space, this study will, on the one hand, take the time interval words into minute analysis to confirm our view of event conceptualization of time at a more basic level along with space–time metaphoric conceptualization of time at a relational level. In alignment with the epistemology of the time–space conflation of the Chinese ancestors, our view is supported by the systematic examination of evidence related to the cultural origins of the conceptualization of time, through a scrutiny of the original meanings and construction of words related to intervals of time in Mandarin Chinese. This study offers a new explanation of how: (1) the conceptualization of time in Chinese is realized through metonymic cognition and (2) words related to specific intervals of time are coined based on the metonymic conceptualization of related events or a corresponding event schema. Five major types of event-based metonymies are identified, and their interactive functions are illustrated. Based on this evidence, we argue that the double nature of both metaphoric and metonymic time conceptualization in Mandarin Chinese lies in the fact that time interval words can be used in its time categorial sense or as a time entity which suggests the etymological origins of Chinese as ideograph. It is concluded therefore that the event-based metonymy conceptualization of time can provide better insights into the characteristics of Chinese modes of thinking and its influences on the perception of and interaction with the world. This study can also serve as good evidence for the shaping effect of language on cognition.